2018
DOI: 10.1002/pola.29276
|View full text |Cite
|
Sign up to set email alerts
|

Chemical modification of poly(lactic acid) induced by thermal decomposition of N‐acetoxy‐phthalimide during extrusion

Abstract: Chemical modification of poly(lactic acid) (PLA) with N‐acetoxy‐phthalimide (NAPI) was performed in the melt by reactive extrusion, without using any peroxide initiator. The aminyl and nitroxide radicals produced from the NAPI thermal degradation, were, respectively, used (a) to create PLA macroradicals, and (b) to functionalize the PLA samples through nitroxide radical coupling. Depending on the extrusion temperature and the initial NAPI concentration, grafting rates up to 0.24 mol % were measured, modifying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…The incorporation of PhM in the PLA during reactive extrusion also had an influence on the final macromolecular structure as revealed by SEC analyses. Indeed, we previously showed that the extrusion of PLA with NAPI led to an important decrease of the PLA average molar masses . As an example, adding 4 mol % NAPI during PLA extrusion led to decreases of 32 and 15 % for M n and M w , respectively, ( M n = 38.1 kg mol −1 ; M w = 73.5 kg mol −1 ; Table ) in comparison to the PLA sample extruded without NAPI ( M n = 55.9 kg mol −1 ; M w = 86.2 kg mol −1 ).…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…The incorporation of PhM in the PLA during reactive extrusion also had an influence on the final macromolecular structure as revealed by SEC analyses. Indeed, we previously showed that the extrusion of PLA with NAPI led to an important decrease of the PLA average molar masses . As an example, adding 4 mol % NAPI during PLA extrusion led to decreases of 32 and 15 % for M n and M w , respectively, ( M n = 38.1 kg mol −1 ; M w = 73.5 kg mol −1 ; Table ) in comparison to the PLA sample extruded without NAPI ( M n = 55.9 kg mol −1 ; M w = 86.2 kg mol −1 ).…”
Section: Resultsmentioning
confidence: 89%
“…PLA was extruded with various PhM concentrations (from 0 to 4 mol %) in the presence of NAPI (Table ), and without any peroxide. Experiments were performed at 200 °C during 30 min, considering our previous results showing that NAPI had a higher degradation rate at an extrusion temperature of 200 °C compared to 180 °C . We also chose to limit the NAPI concentration at 4 mol % (10.2 wt %).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations